Water Loss Monitoring System for Trunk Main System by Water - Jowwongsan, Praewa; Changklom, Jiramate; Pornprommin, Adichai; Jaikaeo, Chaiporn; Lipiwattanakarn, Surachai (RMUTL Engineering Journal, 2022)
Water loss (WL) in water distribution systems (WDS) is a main problem of waterworks in Thailand. A WDS can be divided into a trunk main network (TMN) and a water distribution network. Metropolitan Waterworks Authority (MWA) estimates WL in its TMN about 60-120 million m3/year. Thus, this research presents a monitoring system using the water balance method for 4 routes of the MWA Prachachuen Branch TMN with fairly complete permanent measured flow data from the Remote Monitoring System. Water balance consists of 2 cases: 1) long-term water balance for continuous WL calculation by the data of permanent meters in SCADA systems, and 2) short-term water balance for the case that some flow meters malfunction. By closing water flowing through those meters temporarily at night, WL can be computed for a short period of 2-3 hours. The results show that 1st method can calculate WL if all flow meters work properly. 2nd method can temporarily estimate WL. And both methods estimate WL with a flow discrepancy of tens digit m3/hr. Thus, the system is effective in monitoring leakage on TMN.